Bullock-cart: A Laboratory for Science Teaching - Lambhate, M.V.; Choudhari, U.S. (SCHOOL SCIENCE, 2013)
Science has been made a basic component of our school education, but in the absence of its relation to the life and environment of the learner it has degenerated into a dogma. It is emphasised in the books that “Science is Doing” but it is actually taught in the classroom in the style of history and civics. The teaching of science in school is largely bookish and theoretical. Teachers tell the facts and students note them down, or students read out some passages from the book in the presence of the teacher. In the rural areas the condition is still worse as far as the facilities for teaching science are concerned. But a resourceful and imaginative teacher can still do better if he or she carefully observes and makes use of a variety of materials and apparatus available in the rural environment. To me, a bullock-cart can be a very good laboratory for explaining and demonstrating a number of principles involved in the teaching of physics.